Upper Gastrointestinal Endoscopic and Histopathological Findings in Patients with Dyspepsia - Suzanna Ndraha; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Background: Dyspepsia is a syndrome located in the epigastric area. Upper gastrointestinal (UGI) tract endoscopy and histopathological examination are important diagnostic tools for dyspepsia. This study aimed to evaluate the pattern of dyspepsia in patients who underwent endoscopy examination at Koja Hospital, Jakarta. Method: All patients with dyspepsia who visited Koja Hospital from January until December 2011 were evaluated in this observational study. The data taken was age, gender, clinical symptoms, risk factors, alarm symptoms, body mass index, UGI tract endoscopic and histopathological findings. Data was analyzed using descriptive statistical analysis. Results: Of 1,279 patients with dyspepsia symptoms, 148 patients underwent UGI tract endoscopy. The main symptom was epigastric pain (91.2%). The most common risk factor was female (60.1%). The most common finding of alarm symptoms was history of UGI bleeding (21.6%). The most frequent result of UGI tract endoscopy was gastritis (79.7%). The most widely found of gastritis type was moderate antral gastritis (56%). The most common gastritis histopathological finding was non-active, non- atrophic, non-dysplastic chronic moderate gastritis (56%). All biopsy results included those with gastritis as well as gastric ulcer, which revealed negative results of Helicobacter pylori (H. pylori). Conclusion: The pattern of dyspepsia at Koja Hospital includes female predominant, most patients had alarm symptom history of UGI bleeding, gastritis on endoscopic findings, but H. pylori was not found in histopathological results. Keywords: dyspepsia, symptoms, risk factors, endoscopy, histopathological